2008 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--4201
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Use Of Advanced Fpga Technology In Digital Design Education

Abstract: , IN, teaching in the areas of digital and fault tolerant systems. Her current research interests include fault tolerance and reliability of electronic systems, FPGA design, and new educational methods to teach digital systems design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The students also stated that they tend to apply theories or concepts to practical problems or in new situations in about 85% of the times (Q23). In addition, the students commented that their experience in this course contributed to their knowledge, skills, and personal development for acquiring a broad general education, the average was 3.27 on a scale of [0][1][2][3][4]. Furthermore, the students also indicated that acquiring job or work-related knowledge, and skills and solving complex real-world problems ratings as 3.14 and 3.40 on the same scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The students also stated that they tend to apply theories or concepts to practical problems or in new situations in about 85% of the times (Q23). In addition, the students commented that their experience in this course contributed to their knowledge, skills, and personal development for acquiring a broad general education, the average was 3.27 on a scale of [0][1][2][3][4]. Furthermore, the students also indicated that acquiring job or work-related knowledge, and skills and solving complex real-world problems ratings as 3.14 and 3.40 on the same scale, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Radu [4] emphasized the use of development boards and Coowar [5] elaborated on PLD themselves as well as the CAD tools; however students did not actually construct logic circuits.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…In using CPLDs in our course, we use an integrated approach, which includes the use of schematic capture, CPLDs, breadboards, and the concept of hierarchy. With regard to CAD tools Radu [4] reported that with the inclusion of CAD tools and Field-Programmable Gate Array (FPGA) development boards, they observed a statistically significant increase in student learning. Radu et al emphasized schematics, but also introduced students to a Hardware Description Language (HDL) in the context of code fragments and writing test benches.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%